1992
DOI: 10.1002/dc.2840080503
|View full text |Cite
|
Sign up to set email alerts
|

Cytodiagnosis of lesions presenting as salivary gland swellings: A report of seven cases

Abstract: The cytologic and histologic findings of seven cases presenting clinically as salivary gland swellings are described. These included two cases of pilomatrixoma of skin in the parotid region, two cases of neurilemmoma in the submandibular area, a case of Kimura's disease in the peri-mandibular gland lymphoid tissue, a case of Castleman's disease in intraparotid lymph node, and a case of branchial cleft cyst in the parotid region. It is important to recognize lesions that masquerade as salivary gland tumors so t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 11 publications
1
42
1
1
Order By: Relevance
“…[10] Kimura hastalığında hücresel a tipi hemen hiçbir zaman görülmemiştir. [11,12] Eozinofilik anjiyolenfoid hiperplazi ise daha çok 20-50 yaş aralığında özellikle kadınlarda görülen deri içi lezyonlarla seyreden etyolojisi tam olarak aydınlatılamamış ancak lezyonlarda östrojen reseptörü olması nedeniyle östrojene bağlı bir tümör olduğu düşünülen kronik enflamatuvar bir vasküler hadisedir. [13] Nodüler lezyonlar 2-3 cm'den daha küçük boyutta, pulsatil erimatöz, kaşıntılı ve kırılgan özeliktedir.…”
Section: Discussionunclassified
“…[10] Kimura hastalığında hücresel a tipi hemen hiçbir zaman görülmemiştir. [11,12] Eozinofilik anjiyolenfoid hiperplazi ise daha çok 20-50 yaş aralığında özellikle kadınlarda görülen deri içi lezyonlarla seyreden etyolojisi tam olarak aydınlatılamamış ancak lezyonlarda östrojen reseptörü olması nedeniyle östrojene bağlı bir tümör olduğu düşünülen kronik enflamatuvar bir vasküler hadisedir. [13] Nodüler lezyonlar 2-3 cm'den daha küçük boyutta, pulsatil erimatöz, kaşıntılı ve kırılgan özeliktedir.…”
Section: Discussionunclassified
“…There are several reports in the literature describing its cytologic features and addressing the main differential diagnosis and its diagnostic pitfalls. [3][4][5][6][7][8][9][10][11][12][13][14] However, a review of the literature showed that out of the 34 reported cases, a correct cytologic diagnosis was made in only 12 cases, one of these on repeat FNAB. Most of the cases were reported as carcinoma, mainly squamous cell carcinoma, or suggestive of carcinoma (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…It was described by Woyke et al as eosinophilic clumps, 4 and by Chan and McGuire as birefringent keratin material. 8 Unger et al recognized these masses as compact sheets of ghost cells. 6 Because of their prominent optical characteristic, Wong et al found them to be the most helpful feature in alerting the pathologist to look for ghost cells, leading to the diagnosis of pilomatrixoma.…”
Section: Discussionmentioning
confidence: 99%
“…In the head and neck region they occur most commonly in the internal acoustic meatus, with most of them were benign schwannomas, with only one was reported as malignant schwannoma 4 In our patient, FNAC was not helpful for diagnosis, and we believe FNAC guided by ultrasound is needed for a more informative cytology, as has been reported with other cases 7,8 . The pattern on and MR images shows more of myxomatous tissue which raise a possibility of it not being a simple benign tumour 8,9 Treatment should be confined to complete surgical excision, and wide excision is not recommended. Longterm follow-up of the schwannomas shows few schwannomas recur after complete excision 10 .…”
Section: Case Summarymentioning
confidence: 99%